Kajian Bangunan Bagi Sadap Proporsional Bentuk Numbak di Laboratorium - - Subari; Indri S. Setianingwulan; Bambang Misgiyanta (Jurnal Irigasi, 2013)
The use of the construction for and or diversion structure mostly in the field equipped with a regulating gate, part of the equipment was also used as a proxy for the gate at once. If it does not include the equipment is also equipped with a measuring construction behind it. However, the performance and condition of the existing irrigation are mostly in poor condition, especially the check structure and regulating, it is necessary to divide the structure to change proportionally. In addition, for remote areas and far from the reach of official water control for the proporsional diversion structure operation was helpful disproportionate distribution of irrigation water. The type of the structure could be made for two alternatives, namely the sidewas of diversion and numbak proporsional diversion structure type. The type has a weakness sideways velocity coming straight towards being greater than the lateral direction, so that if the structure is applied proportionately less accurate. While the type has the advantage of speed comes numbak flow is the same for each canal. Type for numbak structure is building for secondary or sub.secondary canal . The purpose of this study to miking of prototype is to obtain of comparison discharge each canal at numbah proportional diversion structure type 1:2:1 proportion. Some test parameters and observations include intake discharge, discharge in each canal, the accuracy threshold measure is used, the validity of the distribution of water in free flow and submerged conditions. Based on hydraulic testing building proportional to the flow conditions for free and submerged flow, proportional according for KP-04 can divide discharge in accordance with the plan. Tests to obtained the proportional distribution of water will be disturbed at low discharge. But it will not affect the high discharge.